APPLICATION OF PARALLEL PROCESSING TO A SURFACE PATCH / WIRE JUNCTION EFIE CODE - Russell, L. C. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
A surface patch / wire junction EFIE method of moment algorithm, JUNCTION, developed by the University of Houston has been implemented in a transputer based parallel processing environment installed in a personal computer. This paper addresses transputer hardware and software options, the JUNCTION algorithm, techniques for parallelizing matrix analysis algorithms, and performance results. The transputer array was found to provide a flexible, low-cost, high performance desktop computing environment for method of moment analysis. [Vol. 7, No. 1, pp. 48-66 (1992)]